Careful return to elective orthopaedic surgery in an acute hospital during the COVID-19 pandemic shows no increase in morbidity or mortality - Monu Jabbal (The British Editorial Society of Bone & Joint Surgery, 2021)
Aims: Elective orthopaedic surgery was cancelled early in the COVID-19 pandemic and is currently running at significantly reduced capacity in most institutions. This has resulted in a significant backlog to treatment, with some hospitals projecting that waiting times for arthroplasty is three times the pre-COVID-19 duration. There is concern that the patient group requiring arthroplasty are often older and have more medical comorbidities—the same group of patients advised they are at higher risk of mortality from catching COVID-19. The aim of this study is to investigate the morbidity and mortality in elective patients operated on during the COVID-19 pandemic and compare this to a pre-pandemic cohort. Primary outcome was 30-day mortality. Secondary outcomes were perioperative complications, including nosocomial COVID-19 infection. These operations were performed in a district general hospital, with COVID-19 acute admissions in the same building. Methods: Our institution reinstated elective operations using a “Blue stream” pathway, which involves isolation before and after surgery, COVID-19 testing pre-admission, and separation of ward and theatre pathways for “blue” patients. A register of all arthroplasties was taken, and their clinical course and investigations recorded. Results: During a seven-month period, 340 elective arthroplasties were performed. There was zero mortality. One patient had a positive swab for COVID-19 while an inpatient, but remained asymptomatic. There were two readmissions within a 12-week period for hip dislocation. Patients had a mean age of 68 years (28 to 90), mean BMI of 30 kg/m2 (19.0 to 45.6), and mean American Society of Anesthesiologists grade of 2 (1 to 3). Conclusion: Results show no increased morbidity or mortality in this cohort of patients compared to the same hospital’s morbidity and mortality pre-COVID-19. The screened pathway for elective patients is effective in ensuring that patients can be safely operated on electively in an acute hospital. This study should reassure clinicians and patients that arthroplasties can be carried out safely when the appropriate precautions are in place. Cite this article: Bone Jt Open 2021;2(11):940–944.